Análise econômica de sistemas produtivos ovinos com diferentes níveis tecnológicos - Barros, Mariana Carvalho de (2023)
The lack of management limits the use of technologies to sheep farms that are not managed with quality compared to other businesses. The objective of the study was to evaluate the economic viability using the deterministic method, of extensive and semi-intensive production systems and simulate an intensive scenario, with technologies applied to sheep farming. Productive systems were characterized, cash flow and costs, economic results and analysis of economic viability were performed on the production period of a sheep cycle for the year 2022. Productive indicators: Pregnancy Rate, Mortality, Weaning and Prolificity were analyzed. Net Margin, Gross Margin, Gross Income, Profit and Profitability were analyzed for financial results. For economic viability analysis, the systems were analyzed comparatively, rejecting all treatments in the sheep business with acquisition of all factors of production , with investments in the acquisition of animals, improvements, land, machinery and working capital. They were refuted given the unfeasibility of this system with negative Net Present Value and Internal Rate of Return indicators, in addition to Payback that extrapolates the 10 years of analysis, declaring loss. Analyzing the sheep business from pre-existing assets, considering the acquisition of animals, working capital and depreciation, a positive NPV was verified according to the intensification of technologies in the systems, IRR surpassing the TMA and Payback lower than the term, according to the systems. The legacy intensive system demonstrates a short Payback time of 2.6 years. Concluding that with the aggregation of technologies the economic viability of the intensive system from pre-existing assets is viable.